Gambaran Asam Urat dan Implikasinya terhadap Kesehatan pada Mahasiswa Universitas Halu Oleo - Irma Yunawati; Nurnashriana Jufri; Wa Ode Salma; Minnati Zulfa Anika; Cantika Alisyah; Dera Kalvio Nita; Amalia Darma Munandar; Della Apriliana Pratiwi (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2025)
Uric acid is the end product of purine metabolism which can cause hyperuricemia if levels increase. Hyperuricemia, if left untreated, can cause joint inflammation, pain, and various other health problems. This study aims to evaluate Halu Oleo University students' understanding of gout and its impact on health. Using a quantitative approach and analytical descriptive design, this research involved 50 randomly selected respondents. Examination of uric acid levels is carried out by taking blood samples using the Nesco Multi Check device. The results showed that 70% of respondents had uric acid levels within normal limits, while 30% experienced hyperuricemia, which indicates a potential risk of developing gout. These findings suggest that unbalanced eating patterns, lack of physical activity, and inadequate fluid intake contribute to increased uric acid levels among college students. This research emphasizes the importance of education about healthy eating patterns and an active lifestyle to prevent health problems related to gout.